2008
DOI: 10.1136/ard.2007.080424
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan regulates the expression of adhesion molecules on circulating T cells and serum soluble adhesion molecules in systemic sclerosis-associated pulmonary arterial hypertension

Abstract: Objectives:To study the expression of adhesion molecules in patients with systemic sclerosis (SSc) with and without pulmonary arterial hypertension (PAH) and the effects of therapy with the endothelin-1 (ET-1) receptor antagonist, bosentan.Methods:In all, 35 patients with SSc and 25 healthy donors (HD) were selected for this study. Of 35 patients, 10 had isolated PAH assessed by Doppler echocardiography and treated with bosentan. Peripheral blood (PB) lymphocytes were isolated by density gradient centrifugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 23 publications
3
52
1
1
Order By: Relevance
“…Endothelin-1 is linked to EC activation in patients with PAH and SSc and is associated with serum levels of soluble adhesion molecules. Therefore, it has been shown that sVCAM-1 and sICAM-1 serum levels were elevated in SSc patients with PAH and decreased after initiation of treatment with endothelin receptor blockers (34). In this study, we could not find an association between serum levels of sVCAM-1 or sE-selectin with the presence of PAH or pulmonary fibrosis in SSc.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Endothelin-1 is linked to EC activation in patients with PAH and SSc and is associated with serum levels of soluble adhesion molecules. Therefore, it has been shown that sVCAM-1 and sICAM-1 serum levels were elevated in SSc patients with PAH and decreased after initiation of treatment with endothelin receptor blockers (34). In this study, we could not find an association between serum levels of sVCAM-1 or sE-selectin with the presence of PAH or pulmonary fibrosis in SSc.…”
Section: Discussioncontrasting
confidence: 72%
“…Moreover, in a study of 31 SSc patients, it has been shown that sVCAM-1 and sE-selectin are related to internal organ involvement of SSc (16 patients with internal organ involvement: 2 patients with PAH, 13 patients with pulmonary fibrosis, and 1 patient with cardiac involvement) (33). Iannone et al showed that sICAM-1, sP-selectin, soluble platelet EC adhesion molecule 1, and sVCAM-1 were elevated in 10 patients with SSc and PAH in comparison to healthy controls (34). Our study shows for the first time that sCD90 serum concentrations are also elevated in patients with SSc and are related to pulmonary involvement.…”
Section: Discussionsupporting
confidence: 57%
“…23 Furthermore, Ang-2 and sPselectin levels in patients with PAH were found to decrease following treatment with intravenous prostacyclin, and the Ang-2 decrease was associated with an improvement in 6MWD. 7,23 Treatment of PAH with the endothelin receptor antagonist bosentan was also associated with a decrease in sP-selectin levels in one study, 24 whereas another study showed an overall increase. 25 In FREEDOM-C2, background PAH therapy was established and stable in all included patients, with the majority already receiving double combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, earlier published studies mainly included therapy-naive patients or patients for whom earlier treatment had shown minimal or no efficacy. 7,8,[23][24][25] One can speculate that the background therapy in FREEDOM-C2 had already influenced the biomarker profile at baseline, resulting in low levels that left little opportunity for further reduction by addition of oral treprostinil. Our sP-selectin data provide some support for this: the mean level in our study population at baseline was 76.6 ng/mL, compared with previously reported baseline levels of 243-367 ng/mL in patients with PAH and 99-132 ng/mL in control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation